ANALISIS PERUBAHAN DAYA DUKUNG LINGKUNGAN BERBASIS JASA EKOSISTEM PENYEDIA AIR DAN PENYEDIA PANGAN DI DAS TABANIO KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Meilawati, Meilawati; Badaruddin, Badaruddin; Rahmadi, Adi; Febrianty, Irma (EnviroScienteae, 2023)
Tabanio Watershed which is one of 4 (four) large watersheds covering 7 (seven) of 11 (eleven) sub-districts in Tanah Laut Regency, has a very large role in providing water which is characterized by the function of the Tabanio river itself as a source of raw material for the PDAM. . In addition, 57.6% of the food comes from paddy fields and dry fields and 66.10% of the food comes from livestock, both cows and broilers, which support food supply in Tanah Laut Regency. Changes in land use over a period of time have reduced catchment areas and water bodies. The purpose of this study was to determine the environmental carrying capacity based on ecosystem services for water and food providers in the Tabanio watershed in 2010, 2015 and 2020 and to determine changes from 2010 to 2015 and from 2015 to 2020. The carrying capacity of the ecosystem services based on the ecosystem services of water and food providers in the Tabanio watershed in 2010, 2015 and 2020 is dominated by the medium classification and has a steady trend, but there is still a decline in ecosystem services from changes in land cover mainly due to the expansion of plantation land which reached 17,257.93 Ha and settlement expansion of 2,272.20 Ha. In addition, there was a decrease in the area of dry land agriculture which reached 20,200.15 Ha.